2014
DOI: 10.1007/s00540-014-1802-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chest compression effect on airway management with air-Q®, aura-i®, i-gel®, and Fastrack® intubating supraglottic devices by novice physicians: a randomized crossover simulation study

Abstract: This simulation study revealed the utility of intubating SGDs for airway management during chest compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…[1,4,11,13,14,2129] All studies were randomized crossover trials except 1 with parallel design. [21] The included articles contained several comparisons between the i-gel and other supraglottic airways as follows: 4 comparisons with the LMA Classic (LMA North America, Inc., San Diego, USA), [11,22,25,29] 5 with the LMA Fastrach (Laryngeal Mask, Prodol Meditec, Spain), [13,14,24,27,28] 3 with the LMA Proseal (LMA North America, Inc., San Diego, USA), [1,14,23] 3 with the LMA Supreme, [13,23,24] 5 with the LMA Unique (LMA North America, Inc., San Diego, USA), [1,4,14,23,24] 7 with the laryngeal tube (King-LT-D, VBM, Sulz, Germany), [1,4,13,14,21,22,24] 5 with the Combitube (Covidien, Mansfield, MA, USA), [1,4,13,14,24] 4 with the EasyTube (Teleflexmedical Ruesch, Research Triangle Park, NC, USA), [1,4,13,24] 1 with the SoftSeal (Smiths Medical International Ltd, Ashford, Kent, UK), [26] 1 with the AuraOnce (Ambu, Ballerup, Denmark), [26] 1 with the aura-i, [27] and 1 with the air-Q (Cookgas LLC, Mercury Medical, USA). [27] Characteristics of the included articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[1,4,11,13,14,2129] All studies were randomized crossover trials except 1 with parallel design. [21] The included articles contained several comparisons between the i-gel and other supraglottic airways as follows: 4 comparisons with the LMA Classic (LMA North America, Inc., San Diego, USA), [11,22,25,29] 5 with the LMA Fastrach (Laryngeal Mask, Prodol Meditec, Spain), [13,14,24,27,28] 3 with the LMA Proseal (LMA North America, Inc., San Diego, USA), [1,14,23] 3 with the LMA Supreme, [13,23,24] 5 with the LMA Unique (LMA North America, Inc., San Diego, USA), [1,4,14,23,24] 7 with the laryngeal tube (King-LT-D, VBM, Sulz, Germany), [1,4,13,14,21,22,24] 5 with the Combitube (Covidien, Mansfield, MA, USA), [1,4,13,14,24] 4 with the EasyTube (Teleflexmedical Ruesch, Research Triangle Park, NC, USA), [1,4,13,24] 1 with the SoftSeal (Smiths Medical International Ltd, Ashford, Kent, UK), [26] 1 with the AuraOnce (Ambu, Ballerup, Denmark), [26] 1 with the aura-i, [27] and 1 with the air-Q (Cookgas LLC, Mercury Medical, USA). [27] Characteristics of the included articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…After intubation through the Aura-i™, it was possible to successfully pass a gastric tube behind the Aura-i™ laryngeal mask with its cuff deflated [11]. A simulation study by novice physicians found that chest compressions did not decrease the ventilation and intubation success rates of four intubating supraglottic airway devices, the AURA-i®, air-Q®, i-gel®, and Fastrack® during cardiopulmonary resuscitation [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Various SGDs exist, and most have an inflatable cuff, including conventional laryngeal masks such as the ProSeal, LMA-Classic, air-Q, and LMASupreme [16]. The ProSeal has various enhanced features and differs from original laryngeal mask models such as the LMA-Classic and LMA-SoftSeal [5].…”
Section: Discussionmentioning
confidence: 99%